THE ROLE OF CHILDREN TO PARENTS A PERSPECTIVE FROM THE QURAN SURAH AL ISRA, VERSES 23-24 - Zazuli, Ahmad; Maula, Ainussyifaul; Fathimah, Ajeng Dewi; Wicaksono, Aji Hanif; Febriani, Evi (FAJAR Jurnal Pendidikan Islam, 2025)
This article discusses the role of children towards parents from the perspective of the Qur'an, especially based on Surah Al-Isra, verses 23-24. In this verse, Allah SWT commands humans to worship only Him and to be kind to both parents with respect and affection. Children are required not to say harsh words such as "ah" or shout at their parents, especially when they are elderly. An attitude of humility, gentleness in speech, and praying for mercy for parents are real forms of filial piety. This command emphasizes the importance of harmonious relationships in the family as a moral and spiritual foundation, while also emphasizing that devotion to parents has a very high position after monotheism to Allah. This article also highlights the implications of moral education contained in this verse, which teaches children to respect and love their parents as a form of gratitude for their services in educating and caring for them since childhood.